2008
DOI: 10.1037/0022-3514.94.5.824
|View full text |Cite
|
Sign up to set email alerts
|

Receiving support as a mixed blessing: Evidence for dual effects of support on psychological outcomes.

Abstract: Although social support is thought to boost feelings of closeness in dyadic relationships, recent findings have suggested that support receipt can increase distress in recipients. The authors investigated these apparently contrary findings in a large daily diary study of couples over 31 days leading up to a major stressor. Results confirm that daily support receipt was associated with greater feelings of closeness and greater negative mood. These average effects, however, masked substantial heterogeneity. In p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

38
372
7
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 303 publications
(422 citation statements)
references
References 64 publications
38
372
7
1
Order By: Relevance
“…This result is inconsistent with previous research showing that received support is associated with worse outcomes on the same day (e.g., Gleason et al, 2008;Maisel & Gable, 2009). However, the studies investigating daily relationships so far included received support within couples.…”
Section: Received Supportcontrasting
confidence: 57%
See 1 more Smart Citation
“…This result is inconsistent with previous research showing that received support is associated with worse outcomes on the same day (e.g., Gleason et al, 2008;Maisel & Gable, 2009). However, the studies investigating daily relationships so far included received support within couples.…”
Section: Received Supportcontrasting
confidence: 57%
“…Second, receiving support from a partner seems beneficial in daily relationships, but only if the support is not noticed by the recipient (Bolger & Amarel, 2007;Bolger, Zuckerman, & Kessler, 2000;Gleason, Bolger, Iida, & Shrout, 2008;Maisel & Gable, 2009;Shrout, Herman, & Bolger, 2006).…”
Section: Explanations For Adverse Effects Of Received Supportmentioning
confidence: 99%
“…We cannot rule out the possibility that this association reflects a reverse causal effect. Gleason (2005) found that providing support may increase intimacy, so it is possible that it is the satisfaction that is following support events, rather than support being facilitated by satisfaction. Our data cannot resolve the direction of these same day effects.…”
Section: Relationship Factorsmentioning
confidence: 99%
“…The data presented here were collected as part of a larger daily diary study designed to examine social support in romantic couples experiencing stress (see Gleason, Iida, Shrout, & Bolger, 2008, for additional details). One member of each couple was a graduating law student preparing for the state bar examination.…”
Section: Design and Participantsmentioning
confidence: 99%
“…Each of these between-subject variables was centered at its grand mean before being entered into the analysis. Finally, to conduct a dyadic analysis, we used the multivariate approach described by Raudenbush and Bryk (2002; see also Gleason et al, 2008) to simultaneously estimate the pattern of results for examinees and non-examinees. This process involves stacking the examinee and non-examinee data and creating a new effect-coded variable to distinguish the two members of the couple.…”
Section: Analytic Approachmentioning
confidence: 99%